PENGEMBANGAN BAHAN AJAR BERBASIS PROBLEM BASED LEARNING PADA MATERI KPK DAN FPB DI KELAS V SD - Widia Anggraini; Hidayat Hidayat (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to develop teaching materials based on Problem Based Learning which are on KPK and FPB material in grade V SD. This research is research development (Research and Development) using the ADDIE development procedure which consists of 5 stages. In this study, researchers carried out the ADDIE development model only up to stage 4, namely Implementation. The instrument used to collect data was a questionnaire or questionnaire given to several expert reviewers, namely expert reviewers of teaching materials, expert reviewers of material, expert reviewers of learning and student responses. The validation score obtained from the material expert reviewer was 88, from the teaching materials expert it was 82, from the learning expert it was 88 and the student response was 95.3. From this score it can be said that the teaching materials based on problem-based learning on the KPK and FPB materials developed are